2014
DOI: 10.1177/1367493514556555
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ perceptions of mobile technology for enhancing asthma care for youth

Abstract: This study assessed physicians' receptivity to using mobile technology as a strategy in patient care for adolescents with asthma. Understanding physicians' perceived barriers and benefits of integrating mobile technology in adolescents' asthma care and self-management is an initial step in enhancing overall patient and disease outcomes. We conducted in-depth interviews with second- and third-year pediatric residents and attending physicians who oversee pediatric residents in training (N = 27) at an academic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 22 publications
4
54
0
Order By: Relevance
“…Prior work has demonstrated that patient access to these technologies is a barrier to providers in recommending them to patients [25][26][27][28], and our results support these findings. Our research demonstrated provider perceived barriers to recommending these technologies included older patients, technical literacy, and financial costs.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Prior work has demonstrated that patient access to these technologies is a barrier to providers in recommending them to patients [25][26][27][28], and our results support these findings. Our research demonstrated provider perceived barriers to recommending these technologies included older patients, technical literacy, and financial costs.…”
Section: Discussionsupporting
confidence: 86%
“…However, Nundy et al found that overall this data is more trustworthy than self-report, which providers perceive that some patients misrepresent their activity to please the providers [26]. In previous research regarding health technologies, Health Insurance Portability and Accountability Act of 1996 (HIPAA) rules and regulations regarding data security have been major concerns among providers [25,27,28]. However, we found the majority of providers were not concerned with these issues.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Previous studies reveal that pediatric asthma patients, their parents, and their pulmonologists desire mobile, user-friendly solutions, such as an app, that tracks their asthma experience, alerts them when their conditions worsen, and strengthens communication among families and their healthcare providers. [21][22][23] The main objective of this study was to engage teen asthma patients in the developmental stages of product design for an asthma self-management app for persons in their age group. We assessed teens' overall impressions of currently available asthma apps.…”
mentioning
confidence: 99%